A Retrospective Study of the Characteristics and Clinical Significance of A-Waves in Amyotrophic Lateral Sclerosis - Fang, Jia; Cui, Liying; Liu, Mingsheng; Guan, Yuzhou; Ding, Qingyun; Shen, Dongchao; Li, Dawei; Tai, Hongfei (Frontiers in Neurology, 2017)
A-wave was observed in patients with motor neuron disease(Rowin and Meriggioli, 2000). However, data on the characteristics and clinical significance of A-waves in patients with amyotrophic lateral sclerosis (ALS) has been scarce. The F-wave studies of 83 patients with ALS and 63 normal participants which were conducted previously at the department of neurology in Peking Union Medical College Hospital were retrospectively reviewed to determine the occurrence of A-waves in ALS. A-waves occurred more frequently in ALS patients than in normal controls. For the median and peroneal nerves, the frequencies of nerves with A-waves and frequencies of patients with A-waves were comparable between the ALS patients and normal controls. For the ulnar and tibial nerves, the frequencies of nerves with A-waves and frequencies of patients with A-waves were significantly increased in the ALS patients compared with those of the normal participants. Disease progression rate was slower in the ALS patients with A-waves (0.73 ± 0.99) than that in the ALS patients without A-waves (0.87 ± 0.55, P = 0.007). No correlations were found between the amplitudes of F-waves with A-waves and those of A-waves in the ulnar nerves (r = 0.423, P = 0.149). No correlations were found between the persistence of F-waves with A-waves and the persistence of A-waves in the ulnar nerves as well (r = 0.219, P = 0.473). The occurrence of A-waves may indicate dysfunction of lower motor neurons and possibly imply a relatively slower degenerative process.